Karakteristik Mushaf Kuno Ibrahim Ghozali Ponorogo - Tri Febriandi Amrulloh; Muhammad Naufal Hakim (Nun : Jurnal Studi Alquran dan Tafsir di Nusantara, 2021)
This article is a study of codicology which aims to representation a characteristics of the Qur’anic manuscript of Ibrahim Ghozali (MKIG). Using a descriptive analytic method, this article has two main analysis, that is the physical of script and the writing style of script. Historically, MKIG has written at 19th century in Polorejo, Ponorogo. Based on the mold of watermark and countermark, showed that the paper used by MKIG is the European paper produced in Heelsum Netherlands in 1808. On writing rasm has found an inconsistency because use of two rasm at once, that is rasm ‘utsmānī and rasm ’imlā’i. While the qirā’at used is the reading of Imām ‘Āṣim narrative H}afś. Based on the characreristics of that writing, MKIG is a mushaf that has a lot of influence from mushaf writing tradition among javaness boarding school. Other side, MKIG is assumed can represent a copy of the mushaf based only on memorization, because found a several corrupt in the form of errors in writing letters and vowels which is exist in almost every surah.